Screening the public sphere : media and democracy in India - Saeed, Saima (Routledge, 2013., 2013)
Part I : Social theory and contours of media : designing news as a body of knowledge -- Part II : Political economy of television news in India : ownership patterns and content -- Part III : Broadcasting in the service of the public : televising Bharat -- Part IV : Television news and civic engagement : implications for democracy and development.